Pengaruh Penerapan Sistem Manajemen Mutu ISO 9001:2008 terhadap Kinerja Karyawan - Vivi Novdya Limbong; Adi Irawan (Journal of Applied Accounting and Taxation, 2019)
Quality standart has became the fundamental parameter for the perfection of every product. Human resource is a valuable assets for the productive company that the quality standart it held should be clearly elaborated to maintain the quality and the work performance remains effective. The following research aims to review how the ISO 9001:2008 quality management system affects the employee's work performance. The 52 respondents of this research consist of production managers and human resource department employees of electricity and elecrtronic companies at Batamindo Muka Kuning, Batam. Data analyzing method used for this research is a simple analytical regression. The research results that the application of ISO 9001:2008 quality management system is effectively affects the employee's performance which goes as the ISO 9001:2008 quality standart procedure. According to the result, it is vital for the company to ensure the continuance of socialization to the whole employee in order to avoid any possible human errors, and to maintain the costumer satisfaction. This research verges on production manager and HRD division of electricity and electronic company at Batamindo Muka Kuning, Batam, therefore, it suggest for the next further research to use the sample from the other company or another district